A Study on “Selfie as an Aesthetic way of Communication among Youth” - G, Priyanga (Journal of Advanced Research in Journalism & Mass Communication, 2018)
In today’s digital world, mobile has become more important in everyone’s life that the situation is without which one cannot survive. Most of the youngsters are having the smartphone with a front camera, which used to take a selfie (a self-portrait photograph of oneself). They also want to post those selfies on social networking site and most of them like to present them in an attractive way. This study is to explore about how adolescent use selfie as a self-representation tool and the usage of makeup apps (You cam, cam cam, beauty plus)as an Aesthetic (appreciation of beauty)way of communication. A quantitative method was employed to understand the minds of youth on selfie among 50 samples in Auxilium College, Vellore, aged between 18-21. Results were analyzed through data interpretation. How to cite this article: Priyanga G. A Study on “Selfie as an Aesthetic Way of Communication among Youth”. J Adv Res Jour Mass Comm 2018; 5(4): 14-25. DOI: https://doi.org/10.24321/2395.3810.201814